Análise da Sustentabilidade da atividade canavieira no município de Pedras de Fogo - PB - Amorim, Bartira Pereira (2013)
The development conception has been related to the idea of economic growth for a long time, however, this conception has became increasingly questioned since, in parallel to the economic growth, the society began to coexist with a socioeconomic and environmental crisis, distant from something that is considered as developed. In this context, the conception of Sustainable Development arises as a solution to the problems faced by society together with the need to use measurement instruments, which are able to establish guidelines for a position in relation to what is expected for a sustainable environment, the sustainability indicators. The discussions about the sustainability aroused a more critical view of social agents regarding environmental issues and the role of productive activities for achieving sustainable goals. In this sense, the agroecosystems and more specifically the activities of the sugar-alcohol sector have presented a key role in the local sustainable development of the regions where these activities are preponderant. Starting from the discussions about the Sustainability Indicators and the performance of the sugar-alcohol sector in aspects related to Sustainable Development, this study was conducted to evaluate the sustainability of the municipality of Pedras de Fogo in Paraíba with emphasis on the sugar-alcohol sector activities, from the indicators system of Barometer of Sustainability. The methodology consisted in two steps: the use of secondary data for collecting information related to the municipality under study, as well as the data for the sustainability indicators to the construction of Sustainable Development Index from the use of the Barometer of Sustainability; and the survey of primary data from interviews with producers and some stakeholders in the sector, through a semi-structured questionnaire. Among the results, it was obtained a sustainability index of 50.23, considered intermediate in the barometer scale, this index is the result of the low income level of the population, the concentration of income that is considered worrisome, the high rates charged for energy provision, besides the deficit in the water supply system in rural area, the extended period of drought that has affected the profitability of producers and the lack of conservation in the region. As well as positive aspects related to population health with regard to the use of agricultural inputs, the representativeness of the agricultural sector to the municipality GDP, the water quality of the region's main reservoir, among other factors. In conclusion, it is highlighted the importance of the government participation aligned to the actions of entities operating in the sector for more effective actions that can be undertaken jointly between private and public sector, as well as the population and development agencies.